O núncio Alessandro Bavona e a criação da província eclesiática de Cuiabá em 1910 (Revista de História Regional, 2021)
This article analyzes the policies and strategies of the Holy See to divide the territory of the diocese of Cuiabá and elevate it to the status of archdiocese, having as suffragans the dioceses of Cáceres and Corumbá. The style of mando of bishop Carlos Luiz d'Amour and his ineffective performance, the large territorial extent of the diocese and its low demographic density motivated the interventions of the Holy See. The expansion of ecclesiastical circumscriptions in Mato Grosso aimed to make their governability more efficient, ensuring the control and regulation of individuals and the social body, implement internal reforms, combat competing religions and strengthen the Catholic Church before the State. The sources were obtained from the Vatican Secret Archives and the Historical Archive of the Congregation on the Extraordinary Ecclesiastical Affairs, that allow detailing the articulations and projects of the nuncio Giuseppe Aversa and secretary of State Raffael Merry Del Val to reform, strengthen and expand the Catholic Church in Brazil.